The Relationship between Speed and Agility on the Football Skills of Young Football Players - Sulistiyono, Sulistiyono; Primasoni, Nawan; Rahayu, Tri Winarti; Galih, Dimas (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
This correlational study aims to determine the relationship between speed and agility on the football playing skills of young players. The sample consisted of 109 players with a mean age of 11.4 years. The sample had an average body weight of 38.5 kg, with a height of 148 cm. The sample had at least 3 months of practice experience in football school. It was conducted by first determining the speed of the players through a 40 m running test. Second, agility was measured a shuttle run test, while the basic football skills were measured using the David Lee skill test. The results showed that there was a relationship between speed, agility, and the football skills of the young players. This proves that football skills alone may not be able to describe the entire performance of players, as speed and agility are also important factors. Therefore, football coaches for young players are expected to pay attention to these factors as supporting components in improving player performance.